The epiqueya in Francisco Suarez's vision (Prudentia Iuris, 2017)
In Book VI of his work De Legibus, Francisco Suárez approaches the study of law, within the framework of the Spanish School of Natural Law. It analyzes the causes for which the law does not apply, among them, the excuse of the obligatory nature of the law by epiqueya (Chapter VII). This is a form of correction of the law in which there is a fault by reason of the universality in front of a concrete case. It inquires about legal fairness as an expression of a fuller justice. The question of etymology, the meaning given by Aristotle and St. Thomas, introduces the study of epiqueya by Doctor Eximius.
Keywords: Suárez; Law; Application; Interpretation; Justice; Epiqueya